2006
DOI: 10.1155/ijp/2006/85927
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous photocatalytic oxidation of lignin and humic acids with supported TiO2

Abstract: The photocatalytic oxidation (PCO) of UV-irradiated aqueous solutions containing humic acids and lignin was studied. The photocatalystTiO2was attached to buoyant hollow glass microspheres and glass plates. A maximum oxidation efficiency as low as1.1and2.54mgW−1h−1for humic acids and lignin, respectively, was achieved in neutral and alkaline media with 25gm−2of the buoyant catalyst. In acidic media, efficiency was even lower. The photocatalytic efficiency with the photocatalyst attached to glass plates was abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 29 publications
4
10
0
Order By: Relevance
“…These values are in line with previous studies related to the photocatalysis with TiO2 25,29,63 , in which was suggested that catalyst concentration should not exceed a value of 2.0 g/L in order to avoid light absorption issues.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…These values are in line with previous studies related to the photocatalysis with TiO2 25,29,63 , in which was suggested that catalyst concentration should not exceed a value of 2.0 g/L in order to avoid light absorption issues.…”
Section: Resultssupporting
confidence: 92%
“…For instance, pH of the aqueous suspension influences the process efficiency having an important role in the formation/inhibition of active hydroxyl radicals. 29 Moreover, catalyst concentration is important for an optimal photocatalytic processing. For example, a catalyst concentration corresponding to 2 g/L has been reported in many studies as the upper threshold value for optimal conditions of the photocatalysis.…”
Section: Introductionmentioning
confidence: 99%
“…In both cases, the maximum PCO efficiency was observed in neutral and slightly basic media (Figure 2), which confirms that the oxidation mechanism with OH-radicals derived from OH-ions may prevail. As was established previously [22], the acidic media were most favourable for lignin adsorption, although are not the best for PCO: the surface concentration at 25 • C decreased from 140 to 30 mg g −1 TiO 2 with the pH increasing from 3.0 to 7.0; at pH 9.0 and above the adsorption of lignin was not observed. As one can see, the PCO efficiency of the attached catalyst behaved consistently with the previous observations made with the TiO 2 attached to buoyant hollow glass microspheres, although reached greater numbers: the PCO efficiency increased, for example, in neutral solutions for about 3.5 times from 2.5 to 9.2 mg W −1 h −1 .…”
Section: The Effect Of Phsupporting
confidence: 67%
“…The glass plates were submerged horizontally in the solution to be treated at a depth from 5 to 10 mm. The results were compared to the data obtained earlier for the photocatalyst attached to hollow glass microspheres [22]. The experiments with visible light were carried out with the suspended TiO 2 -N catalyst made after Gandhe and Fernandes [23].…”
Section: Methodsmentioning
confidence: 94%
“…Humic acids (HAs) are water-soluble compounds with high molecular weight, refractory and characterized as yellow to black in color (Portjanskaja et al 2006). Humic acid represents a fraction of humic substances that is insoluble in water under acidic conditions at pHo2 and soluble at higher pH values (Uyguner & Bekbolet 2005a).…”
Section: Introductionmentioning
confidence: 99%